A Portrait of Teaching and Learning Speaking Strategy at Eighth Grade of English Extracurricular - Ririn Alfiyah; Ahmad Zaeni (International Journal of Education and Humanities, 2021)
Toddlers have behavioral styles or temperaments that affect sensory and motor interactions. This The aim of this research is to know teaching and learning speaking process in English extracurricular in (Sekolah Menengah Pertama/Junior High School). The method which used in this research is qualitative research. The techniques of collecting data that the researcher used are in depth observation and in dept interview to know about teaching and learning speaking in The EAST class as English extracurricular program. The result of this  research  shows  that  teaching  and  learning  speaking  process  in  English extracurricular program is good, because it does with appropirate approach, method, and technique that the tutors used are suitable to the students needed. Therefor, the students have good progress in learning speaking English. The researcher recommend this extracurricular program to be followed by other schools. Because the researcher saw, in common, people have an assumption that a person who master in foreign language is a person who can speak its language. Speaking is interpreted  as  a  fundamental  subject  for  students  develop  a  successful communication  in  language  itself,  which  is  often  the  main  aim  of  learning  any foreign language.  It takes place that teaching  speaking  has a fundamental position to  teacher  helps  students  in  learning  speaking  English.  Therefor,  teaching  and learning speaking has became important for teachers and students to get the aims of speaking, those are to communicate and interact to others.